A new species of Exacum (Gentianaceae) from Western Ghats, India - Geethakumary, M. P.; Pandurangan, A. G.; Ravichandran, P.; Deepu, S. (Phytotaxa, 2016)
Exacum idukkianum (Gentianaceae), a new species from Western Ghats of Kerala, India, is here described and illustrated. This species is similar to E. wightianum, from which it can be distinguished by the perennial habit, with plants up to 2.5 m tall, wingless stem, rectangular curved anthers with cordate base and broadly ovoid capsules. Morphological differences of this species with its putative closest allies with relevant notes and colour plates of the new species are presented.